(untitled) (Eurasian Research Bulletin, 2023)
"Education of a well-rounded individual" is a concept in Uzbekistan’s national education and upbringing history that refers to the development of a well-rounded individual who possesses a strong moral character, intellectual curiosity, and physical fitness. This concept is based on the belief that education should not only focus on academic knowledge but also on the development of a person’s character and personality. The goal of "Education of perfect personality" is to produce individuals who are capable of contributing positively to society and who have the skills and knowledge to succeed in their personal and professional lives. The concept is still an important part of Uzbekistan’s education system today